The Birth of a Nation (Nate Parker, 2016): The Tale of Nat Turner’s Rebellion - Delphine Letort (Transatlantica)
This essay examines the memories of slavery shaped by Nate Parker in The Birth of a Nation. It shows how Parker uses the biopic as a narrative frame to turn the slave rebel into a hero and analyzes the impact of the visuals over the construction of a historically controversial figure. Parker, the essay argues, has devised an aesthetic of slavery that aims to counter the visual legacy of the plantation genre and other existing representations of blackness.